1994
DOI: 10.1152/jn.1994.72.4.1549
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca(2+)-channel currents by protein kinase C in adult rat sympathetic neurons

Abstract: 1. Modulation of Ca(2+)-channel currents by phorbol-12-myristate-13-acetate (PMA) was investigated in acutely dissociated adult rat superior cervical ganglion neurons using the whole cell variant of the patch-clamp technique. 2. PMA (500 nM) increased the current amplitudes, accelerated the inactivation of step currents, retarded the deactivation of tail currents, and shifted the tail current activation to more negative potentials. 3. The effects of PMA were concentration and voltage dependent and mediated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 0 publications
8
65
0
Order By: Relevance
“…In some experiments, reversal of G protein-mediated inhibition was examined using a voltage protocol featuring two steps of 20 ms duration to a test potential of −10 mV, separated by a depolarizing pulse of 40 ms duration to a potential of +70 mV. Voltage protocols similar to this have previously been used to demonstrate relief of G protein-mediated inhibition (Swartz, 1993;Zhu and Ikeda, 1994;Herlitze et al, 1996;Zhu and Yakel, 1997). …”
mentioning
confidence: 99%
“…In some experiments, reversal of G protein-mediated inhibition was examined using a voltage protocol featuring two steps of 20 ms duration to a test potential of −10 mV, separated by a depolarizing pulse of 40 ms duration to a potential of +70 mV. Voltage protocols similar to this have previously been used to demonstrate relief of G protein-mediated inhibition (Swartz, 1993;Zhu and Ikeda, 1994;Herlitze et al, 1996;Zhu and Yakel, 1997). …”
mentioning
confidence: 99%
“…In agreement with this, stimulation of PKC by acute application of phorbol ester causes only minor up-regulation of both channel subtypes, with a net prevalence of the L-type. Since PKC-induced phosphorylation has been proved to disrupt neurotransmitter inhibition on Ca 2+ channels in different neurons and secretory cells [13][14][15][16], we also tested its direct involvement in the Gprotein-mediated noradrenergic inhibition of Ca 2+ channels [17]. The present findings exclude any relation between noradrenergic and PKC-mediated Ca 2+ channels modulation, but underline the essential role of PKC-dependent phosphorylation in tonically maintaining voltage-dependent Ca 2+ channels in a functional state.…”
Section: +mentioning
confidence: 59%
“…Support to this hypothesis comes from studies in central and peripheral neurons [12,13,15,23], where PKC activation is shown to increase Ca 2+ currents by removing the Ca 2+ channels inhibition induced by activated G proteins either tonically or through neurotransmitter receptors. We found, however, that this is not the case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations